STUDY OF THE INFLUENCE OF THE MAIN INDICATORS OF RASPBERRY ON THE VACUUM SUBLIMATION DRYING PROCESS (Proceedings of International Educators Conference, 2023)
This article focuses on the current state of modern drying methods and the practical importance of organizing drying in industry, as well as analytical data on the theoretical basis of drying, the main properties of raspberries and their dependence on drying. Recommendations on the selection criteria of raw materials for drying have also been given.